KNOWLEDGE DEFICIT ABOUT DIETARY NEED IN FAMILIES WITH GOUT ARTHRITIS: A CASE STUDY - Wijayanti, Endah Sri; Iswatun, Iswatun; Sairozi , Ali; Lestari, Feby Diah; Lutfiandini, Cherlys Tin (Universitas Airlangga, 2022)
Introduction: At this time, people with gout arthritis are not only found in the elderly because lifestyles that pay less attention to their health also have a risk of increased uric acid levels in the blood. Gout arthritis is a joint disease caused by increased uric acid levels in the blood, causing several problems. One of the causes of gout is the patient's lack of knowledge about the rules of the gout arthritis diet. The purpose of this study was to carry out family nursing care with a deficiency of understanding of case gout arthritis in Balungtawun Village, Sukodadi District of Lamongan Regency. Methods: The research method used is case study research. The research subjects used five respondents from five family members who had gouty arthritis with knowledge deficit problems in Balungtawun Village, Sukodadi District of Lamongan Regency, using a family nursing process approach. The data was collected through interviews, observation, physical examination, and documentation. The data obtained were analyzed by comparing the theory with cases. Results: The results of the case studies were analyzed, and it was found that there was a match in the process of assessment, diagnosis, intervention, and evaluation. Meanwhile, there are gaps in implementation that are not by the planned intervention. Conclusions: It is expected that families and patients can apply the proper diet for gout arthritis to reduce recurrence and uric acid levels in the patient's blood.